2018
DOI: 10.19173/irrodl.v19i1.3325
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Group Work on the Relationship Between Motivation and Cognitive Load

Abstract: <p class="3">Semi-formal learning is used to describe learning that is directed towards the goals of a formal learning institution but outside of the learning structure of a specific class. Students studying online may form semi-formal groups to increase their knowledge of the content by interacting with other learners taking the same class. This study of cyber university students (n = 2042) involved looking at the relationship between semi-formal learning groups and levels of germane load.  Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
1
8
0
1
Order By: Relevance
“…This falls in line with other research on the topic of collaboration and cognitive load that has shown that collaborative groups are information processing systems that may help students learn as they interact (Jansen et al, 2017). This positive effect on germane load may be generated by several factors that collaboration promotes such as the production of more original notes than if note-taking was done alone (Luo et al, 2016), encoding of information by others (Kiewra, 1989), scaffolding of difficult information (Costley & Lange, 2018), and the self-explanation principle which shows that students who explain something to themselves and/or others will have increased levels of germane cognitive (van Merrienboer & Sweller, 2010). Another factor that may lead to higher levels of germane load is that when learners can give each other feedback, they tend to retain and understand more of what they are taught (Shute, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…This falls in line with other research on the topic of collaboration and cognitive load that has shown that collaborative groups are information processing systems that may help students learn as they interact (Jansen et al, 2017). This positive effect on germane load may be generated by several factors that collaboration promotes such as the production of more original notes than if note-taking was done alone (Luo et al, 2016), encoding of information by others (Kiewra, 1989), scaffolding of difficult information (Costley & Lange, 2018), and the self-explanation principle which shows that students who explain something to themselves and/or others will have increased levels of germane cognitive (van Merrienboer & Sweller, 2010). Another factor that may lead to higher levels of germane load is that when learners can give each other feedback, they tend to retain and understand more of what they are taught (Shute, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…While more than 80% of the universities in the United States offer online courses (Parker, Lenhart, & Moore, 2011), the rate of offering online courses for other countries can go up to 50% in Asia, Africa, and the Middle East (Qayyum & Zawacki-Richter, 2019). The popularity of recent elearning programs stems from their interactive, repetitive, flexible, and customizable nature (Allen & Seaman, 2006;Arkorful & Abaidoo, 2015;Costley & Lange, 2018;Darling-Hammond et al, 2019;Ku & Chang, 2011;Lekawael, 2017;Slater & Davies, 2020;Waschull, 2001). This form of learning has been reported to provide various benefits for the new generation such as expanding access to more learning materials and sources (Hill, 2002;Hofmann, 2002;Li, 2007;Means et al, 2009); providing more affordable education opportunities for the learners that enhance active engagement (Katz & Yablon, 2002;Li, 2007); leading to higher achievement (Katz & Yablon, 2002;Rourke, 2001;Schrum, 2000); and maximizing the learning opportunities among several web-based tools, computer programs, MOOCs, or social media applications and platforms such as Facebook, Twitter, and Instagram (Abney et al, 2018;Aydin, 2012;Chawinga, 2017;Faizi et al, 2013;Fox & Bird, 2017;Wong et al, 2017;Xing, 2019).…”
mentioning
confidence: 99%
“…This indicated that the presence of tutors in the learning video can be extraneous load. This is under the opinion of Costley & Lange (2018) that the high level of extraneous load is generally considered to be detrimental to the germane load, and conversely, the extraneous load can be beneficial to the germane load. This has a slight difference with the results of research conducted by Colliot & Jamet (2018) showing that the presence of a teacher (face and gestures) positively influences students' motivation and involvement in their learning.…”
Section: Resultsmentioning
confidence: 99%